α-Glucosidase, butyrylcholinesterase and acetylcholinesterase inhibitory activities of phenolic compounds from Carthamus tinctorius L. flowers: In silico and in vitro studies - Jawaher A.M. Alotaibi; Alaa Sirwi; Ali M. El-Halawany; Ahmed Esmat; Gamal A. Mohamed; Sabrin R.M. Ibrahim; Abdulrahim A. Alzain; Taher F. Halawa; Martin Safo; Hossam M. Abdallah (Saudi Pharmaceutical Journal)
Chemical investigation of Carthamus tinctorius L. flowers resulted in isolation of seven metabolites that were identified as; p-Hydroxybenzoic acid (1), trans hydroxy cinnamic acid (2), kaempferol-6-C-glucoside (3), astragalin (4), cartormin (5), kaempferol-3-O-rutinoside (6), and kaempferol–3-O-sophoroside (7). Virtual screening of the isolated compounds against human intestinal α-glucosidase, acetylcholinesterase, and butyrylcholinesterase was carried out. Additionally, the antioxidant activity of the bioactive compounds was assessed. Compounds 1 and 5 exhibited moderate binding affinities to acetylcholinesterase (binding energy −5.33 and −4.18 kcal/mol, respectively), compared to donepezil (-83.33kcal/mol). Compounds 1–7 demonstrated weak affinity to butyrylcholinesterase. Compounds 2 and 4 displayed moderate binding affinity to human intestinal α-glucosidase,compared to Acarbose (reference compound), meanwhile compound 2 exhibited lower affinity. Molecular dynamic studies revealed that compound 4 formed a stable complex with the binding site throughout a 100 ns simulation period. The in-vitro results were consistent with the virtual experimental results, as compounds 1 and 5 showed mild inhibitory effects on acetylcholinesterase (IC50s 150.6 and 168.7 µM, respectively). Compound 4 exhibited moderate α-glucosidase inhibition with an IC50 of 93.71 µM. The bioactive compounds also demonstrated notable antioxidant activity in ABTS [2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid)], ORAC (oxygen radical-absorbance capacity), and metal chelation assays, suggesting their potential in improving dementia in Alzheimer’s disease (AD) and mitigating hyperglycemia.